Analysis of the changes of volatile flavor compounds in a traditional Chinese shrimp paste during fermentation based on electronic nose, SPME-GC-MS and HS-GC-IMS - Ying Li; Li Yuan; Huijie Liu; Hongying Liu; Yue Zhou; Miaonan Li; Ruichang Gao (Food Science and Human Wellness)
Traditionally fermented shrimp paste has a long fermentation period and is susceptible of external factors, which leads to unstable quality and limits its development and application. Therefore, the purpose of this study is to analyze the flavor changes in the shrimp paste fermentation process and screen out the key volatile aroma components in the shrimp paste to control the flavor quality of the shrimp paste products. The overall odor profile was detected by the electronic nose. A total of 106 volatile flavor compounds in the shrimp paste samples at different fermentation stages were identified by solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS) and headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS). The main aroma components alcohols, aldehydes, pyrazines and other substances in the fermentation process showed an overall upward trend. A total of 17 key volatile aroma components in shrimp paste at different fermentation stages were identified by the relative aroma activity value (ROAV) method. The combination of electronic nose, SPME-GC-MS and HS-GC-IMS could comprehensively reflect the changes of volatile components in shrimp paste at different fermentation stages, which helps to further understand the mechanism of shrimp paste flavor formation and provides a basis for the regulation of the flavor quality of shrimp paste products.